Accumulation and fluxes of mercury in terrestrial and aquatic food chains with special reference to Finland - Martin Lodenius (European Journal of Environmental Sciences, 2013)
Mercury is known for its biomagnification especially in aquatic food chains and for its toxic effects on different organisms including man. In Finland mercury has formerly been used in industry and agriculture and in addition many anthropogenic activities may increase the mercury levels in ecosystems. Phenyl mercury was widely used as slimicide in the pulp and paper industry in the 1950s and 1960s. In the chlor-alkali industry metallic mercury was used as catalyst at three plants. The most toxic form of mercury, methyl mercury, may be formed in soils, water, sediments and organisms. Many factors, including microbial activity, temperature, oxygen status etc., affect the methylation rate. In the lake ecosystem bioaccumulation of methyl mercury is very strong. In early 1980s there was a restriction of fishing concerning approximately 4000 km2 of lakes and sea areas because of mercury pollution. In aquatic systems we still find elevated concentrations near former emission sources. Long-range atmospheric transport and mechanical operations like ditching and water regulation may cause increased levels of mercury in the aquatic ecosystems. In the Finnish agriculture organic mercury compounds were used for seed dressing until 1992. Although the amounts used were substantial the concentrations in agricultural soils have remained rather low. In terrestrial food chains bioaccumulation is normally weak with low or moderate concentration at all ecosystem levels. Due to a weak uptake through roots terrestrial, vascular plants normally contain only small amounts of mercury. There is a bidirectional exchange of mercury between vegetation and atmosphere. Contrary to vascular plants, there is a very wide range of concentrations in fungi. Mercury may pose a threat to human health especially when accumulated in aquatic food chains.